Percutaneous cryoablation of benign bony tumours of the mandible. Issue 1 (January 2020) - May, L.; Blatter, J.; Bize, P.; Tsoumakidou, G.; Denys, A.; Broome, M.
Abstract: Treatment of bony tumours of the oral and maxillofacial area usually involve resection. However, access to certain areas may be difficult because of the size or site of the tumour. A poor view of the lesion during operation is another limiting factor, which can lead to incomplete resection in difficult cases. Percutaneous cryoablation is a common procedure for treating benign and malignant bony lesions outside the oral and maxillofacial area, but has to our knowledge never been used as a stand-alone treatment as we describe here. In 2016, three patients with benign bony tumours of the mandible (one a keratocyst, one an angiofibroma, and one a giant cell granuloma) were treated with one session of percutaneous cryoablation. Outcomes were monitored with computed tomography or magnetic resonance imaging at one year. No patient had a procedure-related complication, and there were no other complications. Radiological controls showed complete recovery. Percutaneous cryoablation seems to be an interesting and valuable alternative to resection for bony lesions with its limited access and high operative morbidity.